A saúde nas prisões : uma análise constitucional da (in)efetividade dos direitos sociais atrás das grades - Silva Filho, Manoel Bernardino da (2011)
This paper deals with the public health behind bars. The Brazilian health system has failed to protect those who are incarcerated. Although it is a fundamental right protected by various legal instruments, the right to health in prison has been mitigated by the limits of inhumanity. What is defended in the text is the assumption that the enforcement agencies listed among the essential functions of justice State Public Prosecutors and Public Defender - belongs to the legitimate task of promoting this right through the various guarantee arrangements proposed by the Brazilian legislation. It argues, therefore, the possibility of judicial protection of that right, since it considers such issues as: the existential minimum, the reserve for contingencies and human dignity.